Involvement of the Antioxidant Effect and Anti-inflammatory Response in Butyrate-Inhibited Vascular Smooth Muscle Cell Proliferation - Mathew, Omana P. (Pharmaceuticals (Basel), 2014)
Epigenetic mechanisms by altering the expression and, in turn, functions of target genes have potential to modify cellular processes that are characteristics of atherosclerosis, including inflammation, proliferation, migration and apoptosis/cell death. Butyrate, a natural epigenetic modifier and a histone deacetylase inhibitor (HDACi), is an inhibitor of vascular smooth muscle cell (VSMC) proliferation, a critical event in atherogenesis. Here, we examined whether glutathione peroxidases (GPxs), a family of antioxidant enzymes, are modulated by butyrate, contributing to its antiproliferation action on VSMC through the regulation of the inflammatory response by using western blotting, immunostaining methods and activity assay. Treatment of VSMC with butyrate not only upregulates glutathione peroxidase (GPx) 3 and GPx4, but also increases the overall catalytic activity of GPx supporting involvement of antioxidant effect in butyrate arrested VSMC proliferation. Moreover, analysis of the redox-sensitive NF-κB transcription factor system, the target of GPx, reveals that butyrate causes downregulation of IKKα, IKKβ, IkBα and NF-κBp65 expression and prevents NF-κBp65 phosphorylation at serine536 causing inhibition of the expression NF-κB target inflammatory genes, including inducible nitric oxide synthase, VCAM-1 and cyclooxygenase-2. Overall, these observations suggest a link between the antioxidant effect and anti-inflammatory response in butyrate-arrested VSMC proliferation, accentuating the atheroprotective and therapeutic potential of natural products, like butyrate, in vascular proliferative diseases.